Aurora-A kinase is differentially expressed in the nucleus and cytoplasm in normal Müllerian epithelium and benign, borderline and malignant serous ovarian neoplasms - Khaled J. Alkhateeb; Jason E. Crane; Müge Sak; Caitlin J. Jorgensen; James P. O'Donnell; Cory T. Zumbar; Jason A. Wozniak; Clarence R. Salazar; Anil V. Parwani; Norman L. Lehman (BMC, 2021)
Abstract Background Aurora-A kinase is important for cellular proliferation and is implicated in the tumorigenesis of several malignancies, including of the ovary. Information regarding the expression patterns of Aurora-A in normal Müllerian epithelium as well as benign, borderline and malignant epithelial ovarian neoplasms is limited. Methods We investigated Aurora-A expression by immunohistochemistry in 15 benign, 19 borderline and 17 malignant ovarian serous tumors, and 16 benign, 8 borderline, and 2 malignant ovarian mucinous tumors. Twelve fimbriae from seven patients served as normal Müllerian epithelium controls. We also examined Aurora-A protein expression by western blot in normal fimbriae and tumor specimens. Results All normal fimbriae (n = 12) showed nuclear but not cytoplasmic Aurora-A immunoreactivity by immunohistochemistry. Benign ovarian tumors also showed strong nuclear Aurora-A immunoreactivity. Forty-eight percent (13/27) of borderline tumors demonstrated nuclear Aurora-A immunoreactivity, while the remainder (52%, 14/27) lacked Aurora-A staining. Nuclear Aurora-A immunoreactivity was absent in all malignant serous tumors, however, 47% (8/17) demonstrated perinuclear cytoplasmic staining. These results were statistically significant when tumor class (benign/borderline/malignant) was compared to immunoreactivity localization or intensity (Fisher Exact Test, p < 0.01). Western blot analysis confirmed the greater nuclear Aurora-A expression in control Müllerian epithelium compared to borderline and malignant tumors. Conclusion Aurora-A kinase is differentially expressed across normal Müllerian epithelium, benign and borderline serous and mucinous ovarian epithelial neoplasms and malignant serous ovarian tumors., with nuclear expression of unphosphorylated Aurora-A being present in normal and benign neoplastic epithelium, and lost in malignant serous neoplasms. Further studies of the possible biological and clinical implications of the loss of nuclear Aurora-A expression in ovarian tumors, and its role in ovarian carcinogenesis are warranted.